The Role Of Exosomes In Diabetic Polyneuropathy: Pathogenesis And Emerging Therapies - Purbasari, Bethasiwi (Syntax Corporation, 2025)
Diabetic polyneuropathy (DPN) is a common and debilitating complication of diabetes mellitus, characterized by progressive nerve damage, chronic pain, and impaired quality of life. Despite advances in glycemic management, current treatments remain largely symptomatic, underscoring the need for novel therapeutic strategies targeting the underlying pathophysiology. Recent research highlights the critical role of exosomes—nanoscale extracellular vesicles that mediate intercellular communication—in the pathogenesis of DPN. These vesicles transport bioactive molecules (e.g., microRNAs, proteins, lipids) that influence metabolic dysfunction, neuroinflammation, microvascular damage, and impaired nerve regeneration. Exosomes derived from immune cells, Schwann cells, and mesenchymal stem cells (MSCs) exhibit dual roles: propagating nerve injury through pro-inflammatory signaling while also offering therapeutic potential via immunomodulation and neuroprotection. Emerging evidence suggests that exosome-based therapies—such as MSC-derived or engineered exosomes—can promote axonal regeneration, suppress NLRP3 inflammasome activation, and restore nerve function in preclinical models. Furthermore, exosomal biomarkers (e.g., miR-29a, miR-125b) hold promise for non-invasive DPN diagnosis. This review explores the pathogenic mechanisms of exosomes in DPN, their diagnostic potential, and the latest advances in exosome-based therapeutics, while addressing challenges in clinical translation.